DEVELOPMENT OF LEARNING MEDIA SCHOOLOGY BASED ON DISCOVERY LEARNING TO IMPROVE HISTORICAL ANALYSIS - Shohib Furqon Farizi; Nurul Umamah; Sumardi Sumardi (JURNAL HISTORICA, 2020)
Implementation of learning in the Industrial Revolution 4.0 is expected in the learning process using technology. The purpose of this research is to produce a validated product in the form of Schoology Learning media based on Discovery Learning and to improve the ability of Historical Analysis. The development research procedure is carried out using the ASSURE model development. The results of the subject matter content experts reached 80% with "good" qualifications, the learning design expert validation reached 89% with "very good" qualifications and 90% of language validation with very "good" qualifications. Historical Analysis is measured using 4 indicators with small and large group test. In small group trials an increase in students Historical Analysis ability was 77.117% with "high" qualifications and in large group trials an increase in Historical Analysis was 78.73% with "high" qualifications. The benefit of this research is related to Schoology based Dsicovery Learning, Historical Analysis.